Study of the Competitive Situation in the Hotel Market of Samarkand - Azimovna, Musayeva Shoira (Research Parks Publishing LLC, 2022)
This article discusses the marketing strategy, knowledge of marketing distribution channels, available methods of advertising and information work, as well as the size of the estimate. Such a program is usually designed for 3-5 years. The types of promotional and informational events held over the years and their estimated cost in travel companies are shown.